2019
DOI: 10.1101/831891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of genomic-length HBV sequences to determine genotype and subgenotype reference sequences

Abstract: Hepatitis B virus (HBV) is a diverse, partially double-stranded DNA virus, with 9 genotypes (A-I), and a putative 10th genotype (J), thus far characterised. Given the broadening interest in HBV sequencing, there is an increasing requirement for a consistent, unified approach to HBV genotype and subgenotype classification. We set out to generate an updated resource of reference sequences using the diversity of all genomic-length HBV sequences available in public databases. We collated and aligned genomic-length… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…In addition, deletion of viral domains such as the HBV preS region may also contribute towards risks of HCC or recurrence of HCC, such as the recent reports by Teng et al [ 38 ] HBV is currently classified into 10 different genotypes, labeled A to J, which are defined as >7.5% genetic divergence within the full genome sequence of the virus [ 39 , 40 ]. Furthermore, HBV is separated into a number of subgenotypes defined as 4 to 7.5% genetic divergence [ 41 , 42 ]. Traditionally, over 30 different HBV subgenotypes have been identified and classified [ 41 ].…”
Section: Genetic Variations Within Hbvmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, deletion of viral domains such as the HBV preS region may also contribute towards risks of HCC or recurrence of HCC, such as the recent reports by Teng et al [ 38 ] HBV is currently classified into 10 different genotypes, labeled A to J, which are defined as >7.5% genetic divergence within the full genome sequence of the virus [ 39 , 40 ]. Furthermore, HBV is separated into a number of subgenotypes defined as 4 to 7.5% genetic divergence [ 41 , 42 ]. Traditionally, over 30 different HBV subgenotypes have been identified and classified [ 41 ].…”
Section: Genetic Variations Within Hbvmentioning
confidence: 99%
“…Traditionally, over 30 different HBV subgenotypes have been identified and classified [ 41 ]. However, recent studies utilizing powerful sequencing data and phylogenetic analysis have suggested a careful revision of the number and standardization of subgenotypes [ 42 , 43 ]. HBV genotypes are typically geographically distributed.…”
Section: Genetic Variations Within Hbvmentioning
confidence: 99%
“…In addition, as patients with HCC in SSA present at advanced stages, we were unable to recruit individuals with early small tumours, and all patients had tumours >5 cm (data not shown). Finally, whilst our partial HBV sequences (surface genes) are sufficient for genotyping, 3,4 they are not for sub-genotyping as numerous misclassifications will arise, [42][43][44] and this issue needs to be resolved in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…(which was not certified by peer review) published HBV sequences from Bangladesh. Four full-length HBV consensus sequences generated in this study were analysed alongside HBV genotype reference sequences (for genotypes A-J) 42 and 61 sequences originating from Bangladesh identified in Genbank 66 (unlabelled branches, Suppl Table 1). Genotype A sequences are highlighted in blue, genotype C in red and genotype D in yellow.…”
Section: Discussionmentioning
confidence: 99%